A Note on Teaching and Learning Linear Algebra in Tribhuvan University - Nepal, Tulasi Prasad (Journal of the Institute of Engineering, 2019)
The teaching of linear algebra has always been a challenge for teachers of mathematics, because it is extremely important that students become introduced into complex and abstract mathematical system of linear algebra and learn concepts which can be successfully applied later in other mathematical topics. It is necessary that teachers better understand how students learn, and recognize and allow that the appropriate content, methods and context could be different in different environments. As mathematicians, we are aware of the significant interconnections of different ideas and concepts, which is difficult to recognize and understand. We should not forget that understanding of these kinds of interconnections develops through active and hard exploration of mathematical topics through permanent discovering of new interconnections and relations. Thus, primary role of a teacher is to try to move students to take an active part during the class concerning important and difficult concepts, either through the form of individual opinion or through the form of group discussions. It is not easy to suggest teaching methods, especially in comparison to traditional lectures, which would be effective and would actively, engage students and generate stimulating learning.